Inclusive Public Service: The Civil Rights in Administrative Service for Disabilities People at Bojonegoro Regency: JEL Classification: H41, H83, I38, J14, D63, K38 - Putri Indah Prasetyawati; Ana Kumalasari; Musta'ana Musta'ana (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to analyze the fulfillment of civil rights for persons with disabilities in population administrative services, particularly in the issuance of the Identity Card in Bojonegoro Regency. The research employed a qualitative method with a descriptive-analytical approach. Data were collected through in-depth interviews, field observations, and documentation. The findings indicate that the fulfillment of civil rights for persons with disabilities in administrative services still faces various challenges in terms of accessibility, staff competence, and policy implementation. Public service infrastructure remains insufficiently disability-friendly, policy dissemination is limited, and interagency coordination is not yet optimal. Although positive initiatives such as mobile services and social assistance programs have been implemented, these efforts remain partial and have not fully reached all persons with disabilities. The study concludes that fulfilling the civil rights of persons with disabilities in Bojonegoro Regency requires inclusive administrative service reforms, improved staff capacity, and strengthened cross-sectoral collaboration to ensure justice and equal access for all citizens.